2015
DOI: 10.1021/acs.jafc.5b01001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fluoride-Containing Water for the Irrigation of Soil–Plant Systems

Abstract: Many groundwaters used for irrigation contain elevated concentrations of F, but much remains unknown regarding how this F behaves within soils and plants. The present study investigated the adsorption and desorption of F from several soils in short- to medium-term irrigation systems and related foliar F concentrations in three forage plant species to the maximum tolerable level (MTL) in the diets of grazing animals (being 1.8 μmol/g for young cattle, for example). Although adsorption isotherms could be success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Groundwater in many parts of the world is enriched in F - (Edmunds and Smedley, 2013;Ali et al, 2016) and some of these waters are used for irrigation of agricultural land. Scholz et al (2015) found that experimental irrigation of plants with water containing 3 or 5 mg L -1 resulted in little root uptake but there were significant increases of foliar F due to overhead irrigation. The use of F-rich waters to irrigate agricultural land was suggested by Botha et al (1993) to be, in part, responsible for the occurrence of fluorosis in farm animals in a region of South Africa.…”
Section: Other Agricultural Sourcesmentioning
confidence: 97%
“…Groundwater in many parts of the world is enriched in F - (Edmunds and Smedley, 2013;Ali et al, 2016) and some of these waters are used for irrigation of agricultural land. Scholz et al (2015) found that experimental irrigation of plants with water containing 3 or 5 mg L -1 resulted in little root uptake but there were significant increases of foliar F due to overhead irrigation. The use of F-rich waters to irrigate agricultural land was suggested by Botha et al (1993) to be, in part, responsible for the occurrence of fluorosis in farm animals in a region of South Africa.…”
Section: Other Agricultural Sourcesmentioning
confidence: 97%
“…Levels of fluoride vary from 0.02 to 1.2 ppm in Canada (Boyle and Chagnon 1995). The recommended maximum fluoride level in drinking water is 0.7 ppm (World Health 2017, Safe Water 2018) and 2 ppm for agriculture and grazing (Scholz, Kopittke et al 2015). The range of fluoride in the Drayton Valley region was 0 ~ 0.15 ppm, thus met the recommended safety levels, despite fluctuations.…”
Section: Water Qualitymentioning
confidence: 96%
“…These compounds are persistent and resistant to degradation, raising concerns regarding their potential accumulation in soil and water resources [108]. Irrigation with fluorine-rich groundwater can also contribute to fluoride accumulation in plants, particularly via foliar uptake during overhead irrigation [109]. In animals, Botha et al [110] suggested that fluoride-rich irrigation water may be partly responsible for livestock fluorosis in South Africa.…”
Section: Other Agricultural Fluoride Sourcesmentioning
confidence: 99%